Auditing judgment : a book of cases - Johnson, Alan P. (Homewood, Ill. : R. D. Irwin, 1980)
This book is a compilation of literature's that reveals fundamentals in auditing cases. Furthermore, it provides encouragement for professionals accountants.
judgment is the intellectual function which differentiates a profession from a skilled occupation.
Includes bibliographies and indexes.
asm 02/08/19
Loans
Keywords: Auditing; Auditing